Iron and energy metabolic interactions in Treg-mediated immune regulation - Savagner, Frédérique; Farge, Thomas; Karim, Zoubida; Aloulou, Meryem (Frontiers in Immunology, 2025)
Immunometabolism, the study of how metabolic processes influence immune cell function, has emerged as a critical field in understanding the regulation of immune tolerance and the pathological mechanisms underlying autoimmune diseases. Intracellular metabolic pathways not only provide the necessary energy for immune cell survival and activity but also shape the differentiation, phenotype, proliferation, and effector functions of immune cells. This is particularly evident in CD4+ Foxp3+ regulatory T cells (Treg), which are pivotal for maintaining immune homeostasis and preventing autoimmune reactions. Strong experimental evidence highlights the profound impact of metabolism on Treg. Their anti-inflammatory function and ability to suppress excessive immune responses depend on the integration of metabolic cues with their transcriptional and signaling networks. Iron metabolism and mitochondrial dynamics are among the key factors influencing Treg function. This review focuses on how iron and mitochondrial metabolism shape Treg biology and function.